Development of a quantitative ELISA for SARS-CoV-2 vaccine candidate, NDV-HXP-S, with CpG 1018® adjuvant - Marcus Estrada; Changcheng Zhu; Anan Bzami; Jessica A. White; Manjari Lal (Taylor & Francis Group, 2024)
ABSTRACTNDV-HXP-S is a Newcastle disease virus (NDV) vectored vaccine candidate which expresses the S-antigen of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This vaccine candidate is under evaluation in human clinical studies with and without cytosine phosphate guanine (CpG) 1018® adjuvant. Existing potency methods for NDV-HXP-S do not allow for quantification of the S-antigen when the adjuvant is present. To support evaluation of NDV-HXP-S with CpG 1018® adjuvant, an inhibition enzyme-linked immunosorbent assay (ELISA) was developed to allow for quantification and stability assessments of the vaccine. A pilot 6-month stability study was conducted on NDV-HXP-S vaccine with and without CpG 1018® adjuvant under refrigerated conditions (2°C to 8°C) and accelerated stability testing conditions (40°C). The vaccine was mixed with and without CpG 1018® adjuvant in saline and maintained S-antigen content at 2°C to 8°C for the entire 6-month period. Additionally, a pilot controlled temperature chain (CTC) stability study was conducted at the completion of the 6-month study and demonstrated the possibility for this vaccine candidate to attain CTC stability labeling.